Oak Treehopper, Platycotis vittata (Fabricius) (Insecta: Hemiptera: Membracidae) - Frank W. Mead (EDIS, 2005)
The oak treehopper is fairly common on deciduous and evergreen oaks, Quercus spp., where it is sometimes sufficiently abundant to cause concern to owners of valuable shade trees. In Florida we have reports of professional pest control companies being hired to control this pest. However, damage by a colony of this species of treehopper is minor and essentially confined to small oviposition scars in twigs. This contrasts with the closely related thorn bug, Umbonia crassicornis (A. & S.), which can, when abundant, cause considerable dieback or even death of small trees. This document is EENY-328 (originally published as DPI Entomology Circular 57), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2004.